2020
DOI: 10.1111/sjop.12695
|View full text |Cite
|
Sign up to set email alerts
|

Gender and parental involvement in parent‐child reminiscing in a Scandinavian sample

Abstract: Despite the extensive bulk of literature on maternal reminiscing style, only a handful of reminiscing studies have investigated gender differences in parental reminiscing style, with none of these studies having explored the possible relationship between parental involvement level and parental reminiscing style. The current study investigated gender differences in parental reminiscing style across positive and negative event types in an egalitarian Scandinavian context while exploring the potential relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Only a few studies have specifically examined parental differences in reminiscing. Studies with preschoolers, which assess mother-child and father-child reminiscing in dyads, have found that US mothers are more elaborative overall than fathers Zaman & Fivush, 2013), but Svane et al, (2021) found no differences between maternal and paternal elaboration in a Scandinavian sample. It is not clear whether this difference is due to historically changing gender ideologies and behaviors, or to Scandinavian values regarding gender equity.…”
Section: Maternal and Paternal Reminiscingmentioning
confidence: 87%
“…Only a few studies have specifically examined parental differences in reminiscing. Studies with preschoolers, which assess mother-child and father-child reminiscing in dyads, have found that US mothers are more elaborative overall than fathers Zaman & Fivush, 2013), but Svane et al, (2021) found no differences between maternal and paternal elaboration in a Scandinavian sample. It is not clear whether this difference is due to historically changing gender ideologies and behaviors, or to Scandinavian values regarding gender equity.…”
Section: Maternal and Paternal Reminiscingmentioning
confidence: 87%
“…The present study was a part of a larger research programs investigating parent–child verbal interactions (Svane, Kingo & Krøjgaard, 2021; Svane, Olesen et al ., 2021). However, the analyses of the emotional content in the present study is novel and the research question of how parents talk about emotions was not addressed in the other studies based on the same datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Second, and closely related, all of the few existing studies that did include fathers have been conducted in cultures where mothers typically act as the primary caregivers (the Southeastern part of the US, Spain, Turkey). Curiously, to date, no previous studies have explored gender differences in emotional reminiscing in a Scandinavian context where mothers and fathers contribute somewhat equally to childcare (Bonke, Deding, Lausten & Stratton, 2008; Craig & Mullan, 2011; Svane, Olesen, Kingo & Krøjgaard, 2021). Moreover, empirical evidence on how Scandinavian men and women express their emotions, on the whole, and how their emotional expressivity may differ from that of men and women in other cultures is also limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Principe and London (2022) examine how maternal conversational styles and strategies may foster false memories in young children, reflecting the overwhelming emphasis on mothers in studies of parent–child conversational exchanges (Fivush, 2014). Traditional fathers appear to adopt different conversational styles with their children (Leaper et al, 1998; Zaman & Fivush, 2013), and it would be interesting for both researchers and forensic professionals to know whether contamination is equivalently likely in conversations with mothers, fathers, teachers, and other adults, especially when different parenting figures adopt different parenting roles (Svane et al, 2021), as well as whether there are cultural and subcultural variations (Wang, 2021a, 2021b).…”
mentioning
confidence: 99%